Pengaruh Pola Komunikasi Antara Fisioterapis dengan Orangtua Terhadap Perkembangan Motorik Anak Usia 0-12 Bulan di Griya Fisioterapi Mandiri Semarang - Fitratun Najizah; Shella Dhika Rahmawati; Cintya Putri Anisah; Sofia Mardiana (Jurnal Medical Laboratory, 2024)
Conversation is a common pattern of interaction between physiotherapists and patients. However, in child growth and development therapy, where the patient is a child aged 0-12 months, of course communication behavior involves the parents. The pattern of interaction between physiotherapists and patient parents in relation to the child's growth and development is what is studied in this research. This research was carried out with the aim of assessing the influence of communication patterns between physiotherapists and parents on the motor development process of children aged 0-12 months. In pediatric cases, the communication pattern between physiotherapists and parents is a medium that can be useful in the process of exchanging information both in stimulating children's growth and development and in matters related to other children's motor development processes. This is due to differences in the conditions of each child which will make parents and physiotherapists experience problems when carrying out therapy sessions. Through statistical tests, this research succeeded in concluding that there is a significant relationship between the intensity of parental communication on the process of motor development of children aged 0-12 months in the process of growth and development therapy.